The effect of average length of schooling, life expectancy, and labor force participation rate on the provincial Human Development Index (HDI) in 34 provinces of Indonesia, 2020 - Amelia Nuraisah; Destira Putri Andita; Ahmad Sabaha; Muhammad Farrel Shidqii; Nelwan Satrio Gunawan (PT Aksara Indo Rajawali, 2025)
This study aims to analyze the effect of Average Length of Schooling (ALS), Life Expectancy (LE), and Labor Force Participation Rate (LFPR) on the Human Development Index (HDI) in Indonesia in 2020. This paper is a quantitative study employing a multiple linear regression analysis. The data that is applied in the present research is secondary data, which is official publications of the Central Statistics Agency (BPS) of 2020. The level of significance (alpha) used was 0.05 to find out the impact of each variable. The findings reveal that, to a certain extent, the Human Development Index is significantly influenced by the Average Length of Schooling and Life Expectancy, and there is no significant influence of Labor Force Participation Rate. Simultaneously, these three variables are proven to affect the Human Development Index, indicating that education, health, and labor conditions remain important components in supporting human development. Overall, these findings highlight that improving the quality of education and health plays a more dominant role in increasing Indonesia's Human Development Index in 2020 compared to the aspect of labor force participation.